A Case Study on Consumers’ Buying Behaviour and Brand Loyalty with Regard to Processed Liquid Packed Milk in Guwahati, Assam - Kumar, Brajesh; Gogoi, Mintu (Indian Journal of Marketing, 2011)
The present study has been undertaken to examine the consumer’s buying behavior and brand loyalty with regard to processed liquid packed milk in Guwahati. Understanding consumer buying behavior in a cross-cultural environment is an essential part of marketing activities in a world that is becoming more consumer-centric. Studying the consumer buying behavior is a very complex process, as it involves not only the economic factors, but also the emotional factors. However, marketers need to study the consumer behaviour, as it helps them to position their products better and develop effective marketing strategies. Consumer buying behaviour is influenced by the culture and subculture. Habits, likes and dislikes of the people belonging to a particular culture or subculture can affect the marketing efforts of a firm to a great extent. The social class to which the individual belongs tells about the type of products the individual prefers. Other factors that influence the buying behavior are social factors like reference group and family, personal factors like the age, life cycle and occupation, and psychological factors like motivation, perception and attitudes of the customers. This paper is an attempt to explain how consumer buying behaviour is influenced by brand image and loyalty in Guwahati, Assam. On the basis of the study, it emerged that consumer satisfaction needs to be observed as the function of some dynamic variables, which needs concurrent monitoring for better marketing results.